Encapsulation of doxorubicin prodrug in heat-triggered liposomes overcomes off-target activation for advanced prostate cancer therapy. (1st March 2022) - Pereira, Sara; Ma, Guanglong; Na, Li; Hudoklin, Samo; Kreft, Mateja E.; Kostevsek, Nina; Al-Jamal, Wafa T.
Abstract: L-377, 202 prodrug consists of doxorubicin (Dox) conjugated to a prostate-specific antigen (PSA) peptide substrate that can be cleaved by enzymatically active PSA at the tumor site. Despite the initial promise in phase I trial, further testing of L-377, 202 (herein called Dox-PSA) was ceased due to some degree of non-specific activation and toxicity concerns. To improve safety of Dox-PSA, we encapsulated it into low temperature-sensitive liposomes (LTSL) to bypass systemic activation, while maintaining its biological activity upon controlled release in response to mild hyperthermia (HT). A time-dependent accumulation of activated prodrug in the nuclei of PSA-expressing cells exposed to mild HT was observed, showing that Dox-PSA was efficiently released from the LTSL, cleaved by PSA and entering the cell nucleus as free Dox. Furthermore, we have shown that Dox-PSA loading in LTSL can block its biological activity at 37°C, while the combination with mild HT resulted in augmented cytotoxicity in both 2D and 3D PC models compared to the free Dox-PSA. More importantly, Dox-PSA encapsulation in LTSL prolonged its blood circulation and reduced Dox accumulation in the heart of C4-2B tumor-bearing mice over the free Dox-PSA, thus significantly improving Dox-PSA therapeutic window. Finally, Dox-PSA-loaded LTSL combined with HT significantly delayed tumor growth at a similar rate as mice treated with free Dox-PSA in both solid and metastatic PC tumor models. This indicates this strategy could block the systemic cleavage of Dox-PSA without reducing its efficacy in vivo, which could represent a safer option to treat patients with locally advanced PC. Statement of significance: This study investigates a new tactic to tackle non-specific cleavage of doxorubicin PSA-activatable prodrug (L-377, 202) to treat advanced prostate cancer. In the present study, we report a nanoparticle-based approach to overcome the non-specific activation of L-377, 202 in the systemic circulation. This includes encapsulating Dox-PSA in low temperature-sensitive liposomes to prevent its premature hydrolysis and non-specific cleavage. This class of liposomes offers payload protection against degradation in plasma, improved pharmacokinetics and tumor targeting, and an efficient and controlled drug release triggered by mild hyperthermia (HT) (∼42°C). We believe that this strategy holds great promise in bypassing any systemic toxicity concerns that could arise from the premature activation of the prodrug whilst simultaneously being able to control the spatiotemporal context of Dox-PSA cleavage and metabolism. Graphical abstract: Image, graphical abstract